Biosynthesis of Poly Acrylic Acid (PAA) Modified Silver Nanoparticles, Using Basil Leaf Extract (Ocimum basilicum L.) for Heavy Metal Detection - Yussi Pratiwi; Yusmaniar Yusmaniar; Nurhasanah Nurhasanah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
This study focused on characterizing synthesized silver nanoparticles (AgNPs) and evaluating their efficacy as colorimetric detectors for heavy metal ions. The synthesis employed a bottom-up approach, using AgNO3 as a precursor, reduced by secondary metabolites in basil leaf extract, enhanced with Polyacrylic acid (PAA). Basil leaves were chosen for their rich content of secondary metabolites like phytosterols, alkaloids, phenolic compounds, tannins, lignin, starch, saponins, flavonoids, terpenoids, and anthraquinones, crucial in reducing silver ions. Incorporating basil leaf extract as a bioreactor and adding PAA to increase stability and selectivity towards metal ions are innovative aspects of this research. The optimal AgNP composition was attained with a 0.7 mL basil leaf extract to 10 mL AgNO3 ratio plus 2% PAA. The AgNP formation was indicated by a color change from yellow to brownish, with a Surface Plasmon Resonance (SPR) peak at 418 nm. Characterization via Fourier Transform Infrared Spectroscopy (FTIR) revealed hydroxyl (-OH) and carbonyl (C=O) functional groups aiding in silver ion reduction. Particle Size Analysis (PSA) showed AgNPs of 72.3 nm size, with a polydispersity index of 0.504. Colorimetric detection tests were conducted on Cu(II), Pb(II), Cd(II), Zn(II), and Mn(II) ions. AgNPs exhibited high reactivity towards Cu2+, changing color from brownish to clear white within a minute upon Cu2+ addition, unlike Cd2+, Mn2+, Zn2+, and Pb2+, which showed negligible changes. This indicates a heightened sensitivity of AgNPs to Cu2+ ions. Such a colorimetric sensor could be instrumental in detecting heavy metals in drinking water, showcasing the potential application of AgNPs in environmental monitoring.